The role of the dentist in home visits of patients with disabilities (Research, Society and Development, 2022)
Objective: analyze the oral health conditions of patients with disabilities in the Morumbi district of Cascavel-PR county, through home visits carried out by the Family Health team, in addition to analyzing the limitations that these patients face in relation to access and maintenance of oral health, with these restrictions being accentuated due to the Covid-19 pandemic. Methodology: From the dental records of patients with disabilities, information was obtained in relation to the types of disabilities, anamnesis, physical examination, oral health risk stratification and conduct performed on the day of the home visit. Results: Of the 41 records analyzed, there was a higher prevalence of female patients (59%), elderly (52%) and with physical disabilities (51%). Most patients also need caregiver(s) (80%). Of the patients who have dental prosthesis, most do not perform their hygiene and care properly (93%) and, of those who have natural teeth, most do not use dental floss (81%). In addition, several do not have a previous record of dental care in a health unit in the last 4 years (76%). Conclusion: Due to the impediments that arose during the execution of the home visits, home care and oral health guidelines should be provided to the rest of the patients who were left unattended, emphasizing the importance of the dentist in ensuring continuous care for these patients.